Enhancing Antibacterial Activity through Structural Modification by Benzenesulfonylation of Methyl \(α\)-D-Glucopyranoside - Sarkar M. A. Kawsar (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
The significance of carbohydrates necessitates the development of a new approach to producing prescription drugs based on carbohydrates in the current context of global health and illness. This study investigated the synthesis of a novel series of benzenesulfonyl derivatives of methyl \(α\)-D-glucopyranoside (MGP) by reacting benzenesulfonyl chloride in pyridine followed by direct acylation to yield a 6-O-benzenesulfonyl derivative (2). To obtain newer products for antibacterial evaluation studies, the 6-O-benzenesulfonyl derivative was further transformed into a series of 2,3,4-tri-O-acyl derivatives (3–11) containing a wide variety of functionalities in a single-molecule framework. To determine the structures of these derivatives, spectral and elemental analyses were performed. In vitro, antibacterial screening was performed against two gram-positive and two gram-negative human pathogenic bacterial strains. The D-glucopyranoside derivatives exhibited moderate to good antibacterial activities. Interestingly, the proposed compounds showed greater sensitivity against gram-negative bacteria than against gram-positive bacteria. In conclusion, the outcomes of this work indicate that benzenesulfonyl-based MGP compounds have significant potential as antibacterial agents for treating infectious diseases.